2020
DOI: 10.1111/cid.12950
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional analysis of dimensional changes after alveolar ridge preservation with bone substitutes or plasma rich in growth factors: Randomized and controlled clinical trial

Abstract: Objectives To evaluate alveolar ridge dimensional changes of different alveolar ridge preservation techniques after 3 months of tooth extraction and to compare the efficacy of autologous plasma rich in growth factor (PRGF) to the bone substitutes in alveolar ridge preservation and sites left to heal spontaneously. Materials and Methods Forty patients requiring tooth extraction in the anterior maxilla were randomly allocated to the four following treatment modalities: spontaneous healing (control), natural bovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(60 citation statements)
references
References 50 publications
1
58
0
1
Order By: Relevance
“…Our results were in line with these findings, with a value of 1.49 mm in the control group and 0.63 mm in the experimental group. The similar results were showed in the RCT of PRGF compared with bone graft materials 46 . The low value in our study may be attributable to differences in study inclusion criteria, although further work is required to fully understand any potential differences between these analyses.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our results were in line with these findings, with a value of 1.49 mm in the control group and 0.63 mm in the experimental group. The similar results were showed in the RCT of PRGF compared with bone graft materials 46 . The low value in our study may be attributable to differences in study inclusion criteria, although further work is required to fully understand any potential differences between these analyses.…”
Section: Discussionsupporting
confidence: 77%
“…The similar results were showed in the RCT of PRGF compared with bone graft materials. 46 The low value in our study may be attributable to differences in study inclusion criteria, although further work is required to fully understand any potential differences between these analyses. Several studies have reported ridge width changes at 1, 3, and 5 mm below the crest, 30,44,47 with diminishing changes and reduction rates.…”
Section: Discussionmentioning
confidence: 84%
“…Cone-beam computed tomography emerged in the late 1990s, when the overlap found in two-dimensional radiographic examinations made it difficult to visualize deeper structures 5 . In this way, the technology brought the X-ray beam is projected conically at a fixed point, with the formation of several images segmented in cuts in the three-dimensional planes [12,15], allowing the detailed anatomical visualization, in addition to the optimization of the visual resources of the image and its spatial manipulation [5].…”
Section: Conical Beam Computerized Tomography (Cbct)mentioning
confidence: 99%
“…In this regard, it is necessary to identify ideal situations for the use of cone beam or fan beam techniques, knowing the specific indication for each one and its applicability, its advantages and disadvantages [14,15,16,17], in addition to a comparison between Cone Beam Computed Tomography and Spiral Computed Tomography in the field of dentistry regarding Oral and Maxillofacial Surgery and Traumatology [9].…”
Section: Introductionmentioning
confidence: 99%
“…Today there is great interest in autologous platelet gel, platelet concentrates (PC), and growth factors. They are extensively used in endodontic [ 17 ], oral surgery, in implantology [ 18 ] and parodontology [ 19 ]. Platelet concentrates (PC) have been widely used in bone regenerative procedures for their autologous origin and they offer a great concentration of platelets, when compared to the concentration in natural blood.…”
Section: Introductionmentioning
confidence: 99%